Color temperature and its role within the artificial lighting of initial education spaces - Vera Mazuelos, Gabriela Alexandra (2021)
Early childhood education centers are the first space that children inhabit after home and are an essential part of their development. In this sense, the research analyzed the relationship between the color temperature present in artificial lighting systems in early childhood education spaces and different areas of child development in children from 0 to 5 years old. With the aim of demonstrating that, through the control of color temperature in artificial lighting systems, various areas of child development can be stimulated. Criteria within the physical, cognitive, psychomotor and sensory development of early childhood children and the qualities of color temperature were analyzed. In this way, a proposal for dynamic lighting is proposed that stimulates areas of child development through light scenes. In this sense, artificial lighting becomes a resource that can be used to stimulate activities carried out in initial education spaces and can become a design tool, with the aim of achieving a stimulating environment.